SNAP25 protects primary cortical neurons from hypoxic‐ischemic injury associated with CREB signal. Issue 1 (28th March 2021) - Jin, Yuan; Zhang, Chao; Fang, Xu; Fang, Chang‐Le; Chen, Jie; Du, Ruo‐Lan; Hu, Qiao; Dong, Liang; Zhu, Zhao‐Qiong; Wang, Ting‐Hua
Abstract : Background: Hypoxic‐ischemic encephalopathy (HIE) could induce exacerbated changes and unpredictable effects in brain cells, and the mechanism remains unclear. Methods: HIE model was established in neonatal rats, Zea‐Longa score and TTC staining were used to observe the neurobehavior and brain infarct volume in rats subjected to cerebral hypoxia‐ischemia (HI). Primary cortical neurons were then cultured in vitro to establish an oxygen and glucose deprivation model. To determine the role of synaptosomal‐associated protein‐25 ( SNAP25 ) in HIE, PC12 cells were cultured and effective siRNA fragments were screened, and SNAP25 was transfected into primary neurons. Then, quantitative real‐time polymerase chain reaction was used to detect the mRNA expression level and immunofluorescence staining was used to observe the morphological changes of neurons before and after the injury. Finally, the abundance values of SNAP25 and its associated genes were filtered using the NCBI and GeneMANIA, respectively. Results: HI leads to a decrease in neuronal number and an increase in SNAP25 expression. Whereas, the interference of SNAP25 caused marked decrease in neuronal number and the length of neurite. Moreover, the expression levels of CREB and SYP were significantly decreased after interference of SNAP25 . Conclusion: SNAP25 exhibited several neuroprotective effects to neuronal protection in neonatal cerebral HI by regulating CREB and SYP.